2009
DOI: 10.1021/jp902978r
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Different Anions on the Surface Composition of Ionic Liquids Studied Using ARXPS

Abstract: Angle-resolved X-ray photoelectron spectroscopy has been used to study the influence of different types of anions on the surface composition of ionic liquids (ILs). We have investigated nine ILs with the same cation, 1-octyl-3-methylimidazolium [C(8)C(1)Im](+), but very different anions. In all cases, an enrichment of the cation alkyl chains is found at the expense of the polar cation head groups and the anions in the first molecular layer. This enhancement effect decreases with increasing size of the anion, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

31
263
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 175 publications
(296 citation statements)
references
References 53 publications
(161 reference statements)
31
263
1
Order By: Relevance
“…IL1 has already been discussed in literature 44, 45, 46. For this IL, a significant increase of the C alkyl is observed at 80°, that is, the signal at 80° increases by about 22 % (see SI, Figure S1).…”
Section: Resultssupporting
confidence: 55%
See 3 more Smart Citations
“…IL1 has already been discussed in literature 44, 45, 46. For this IL, a significant increase of the C alkyl is observed at 80°, that is, the signal at 80° increases by about 22 % (see SI, Figure S1).…”
Section: Resultssupporting
confidence: 55%
“…The neat IL1 and IL2 have already been studied in detail in the past, and a pronounced protruding of the alkyl chains towards the vacuum has consistently been reported 44, 45, 46. On the other hand, we are not aware of any previous XPS studies of IL3, which contains the very specific [(MeO) 2 Im] + cation.…”
Section: Resultsmentioning
confidence: 91%
See 2 more Smart Citations
“…Kolbeck et al observed spectral changes in their XPS measurements for many [OMIm]-based ILs after extended exposure to X-rays. 13 Most changes appeared in the N1s region at binding energies lower than that of the imidazolium nitrogen. They also suggested the presence of uncharged decomposition products.…”
Section: This Journal Is C the Owner Societies 2011mentioning
confidence: 99%